EVALUATION OF ANTIOXIDANT, ANTIMICROBIAL, ANTICANCER, AND WOUND HEALING PROPERTIES OF LEAF EXTRACTS OF ACANTHUS ILICIFOLIUS L. - A., SHAMEELA KHADEEJA; JOHNEY, JESTEENA; RAGUNATHAN, R. (International Journal of Current Pharmaceutical Research, 2023)
Objective: To investigate the in vitro antioxidant, antimicrobial, anticancer, and wound healing properties of leaf extracts of Acanthus ilicifolius. Methods: Acanthus ilicifolius leaves were dried and extracts were prepared using different solvents using cold extraction method. The preliminary phytochemical analysis and quantitative methods were carried out using standard procedures. In vitro antioxidant activity was evaluated using DPPH assay. Disc diffusion method was employed to determine the antimicrobial activities of the extracts. The methanolic extract was subjected to FTIR and GC-MS analysis for characterization of phytochemicals. This extract was further subjected to HPLC analysis for characterization and quantification. The antiproliferative effects of methanolic extract was determined using MTT assay and wound healing properties were determined using Cell migration assay. Results: The highest levels of phenol and flavonoids were detected in aqueous extracts, followed by chloroform. Methanolic extract showed the highest antioxidant activity as well as significant antibacterial activity against Klebsiella pneumoniae and Staphylococcus aureus. Squalene, a metabolite with known pharmaceutical applications, was identified in GC-MS, which was further confirmed and quantified using HPLC analysis. The methanolic extract showed cytotoxic activity against the cervical cancer cell line and showed a significant beneficial effect on wound healing in the L929 cell line. Conclusion: The results obtained in this study revealed that the leaf extracts of Acanthus ilicifolius possess potent antioxidant, antimicrobial, cytotoxic and wound-healing properties. These activities are due to bioactive components present in the extracts whose identification could lead to the development of new therapeutic agents.